Detection of Zak phases and topological invariants in a chiral quantum walk of twisted photons - Filippo Cardano; Alessio D’Errico; Alexandre Dauphin; Maria Maffei; Bruno Piccirillo; Corrado de Lisio; Giulio De Filippis; Vittorio Cataudella; Enrico Santamato; Lorenzo Marrucci; Maciej Lewenstein; Pietro Massignan (Nature Communications, 2017)
The detection of topological invariants in the bulk remains challenging even in state-of-the-art experiments. Here, Cardanoet al. propose a method to read-out the Zak phases and topological invariants in one-dimensional chiral systems and detect those in a photonic quantum walk of twisted photons.